Perilipin 5 deficiency aggravates cardiac hypertrophy by stimulating lactate production in leptin-deficient mice - Lele Jian; Xing Gao; Chao Wang; Xiao Sun; Yuqiao Xu; Ruili Han; Yuying Wang; Shenhui Xu; Lan Ding; Jingjun Zhou; Yu Gu; Yuanlin Zhao; et al. (Biology Direct, 2023)
Abstract Background Perilipin 5 (Plin5) is well known to maintain the stability of intracellular lipid droplets (LDs) and regulate fatty acid metabolism in oxidative tissues. It is highly expressed in the heart, but its roles have yet to be fully elucidated. Methods Plin5-deficient mice and Plin5/leptin-double-knockout mice were produced, and their histological structures and myocardial functions were observed. Critical proteins related to fatty acid and glucose metabolism were measured in heart tissues, neonatal mouse cardiomyocytes and Plin5-overexpressing H9C2 cells. 2-NBDG was employed to detect glucose uptake. The mitochondria and lipid contents were observed by MitoTracker and BODIPY 493/503 staining in neonatal mouse cardiomyocytes. Results Plin5 deficiency impaired glucose utilization and caused insulin resistance in mouse cardiomyocytes, particularly in the presence of fatty acids (FAs). Additionally, Plin5 deficiency increased the NADH content and elevated the expression of lactate dehydrogenase (LDHA) in cardiomyocytes, which resulted in increased lactate production. Moreover, when fatty acid oxidation was blocked by etomoxir or LDHA was inhibited by GSK2837808A in Plin5-deficient cardiomyocytes, glucose utilization was improved. Leptin-deficient mice exhibited myocardial hypertrophy, insulin resistance and altered substrate utilization, and Plin5 deficiency exacerbated myocardial hypertrophy in leptin-deficient mice. Conclusion Our results demonstrated that Plin5 plays a critical role in coordinating fatty acid and glucose oxidation in cardiomyocytes, providing a potential target for the treatment of metabolic disorders in the heart. Graphic abstract